Normal pregnancy outcome in a woman with chronic myeloid leukemia and epilepsy: a case report and review of the literature - Sahin, Levent; Aygun, Banu Kumbak (Walter de Gruyter Gmbh, 2012)
Introduction: The management of chronic myeloid leukemia (CML) during pregnancy is a matter of continued debate. Imatinib therapy for CML might be associated with fetal anomalies and discontinuation of the drug with disease progression. We present the achievement and management of a pregnancy in a woman with both CML and epilepsy. We describe the first uneventful pregnancy and successful delivery of a healthy, normal baby in a patient with CML and epilepsy. Case report: A 25-year-old woman with both CML and epilepsy presented with infertility to our in vitro fertilization unit. She has CML diagnosed 5 years ago and epilepsy 9 years ago. She was on imatinib therapy for CML and valproic acid therapy for epilepsy. She became pregnant with ovulation monitoring in a spontaneous cycle. Because the patient was asymptomatic and stable, she stopped imatinib therapy and was observed with only a single antiepileptic drug, valproic acid, during the entire pregnancy. No problem occurred during the pregnancy, and she delivered a healthy baby by cesarean section at 38 weeks' gestation. Conclusion: The management of CML during pregnancy might be individualized on the basis of clinical manifestations, and close observation without any intervention may be an option after proper counseling of the patient. A healthy birth is possible in a well-controlled pregnancy in a woman with both CML and epilepsy.
Keywords: Chronic myeloid leukemia; epilepsy; pregnancy